2022
DOI: 10.3389/fcvm.2022.814610
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Cardiovascular Health in Young Adults With Established Cardiovascular Diseases

Abstract: There has been an increase in the prevalence of cardiovascular diseases among young adults in the United States that has been attributed, in part, to a rise in overweight and obesity, use of combustible tobacco and unhealthy diet and exercise patterns. These factors are influenced further by socioeconomic status and other social determinants of health. In the My Research Legacy study, we examined ideal cardiovascular health in young adults aged 18– <50 years with cardiovascular disease using the Life's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…there was a decrease in the prevalence of hyperlipidemia, potentially reflecting greater regulation on the use of transfatty acids and other partially hydrogenated oils. 27,28 Overall, our findings highlight the need to intensify public health and clinical interventions focused on primordial and primary prevention for young adults, 1,29 given evidence that cardiovascular disease mortality may now be rising in this population, as well as the potential adverse long-term public health impact of these trends in risk factors on lifetime rates of acute myocardial infarction, stroke, and heart failure. [17][18][19]30 We also observed significant variation in cardiovascular risk factors across racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…there was a decrease in the prevalence of hyperlipidemia, potentially reflecting greater regulation on the use of transfatty acids and other partially hydrogenated oils. 27,28 Overall, our findings highlight the need to intensify public health and clinical interventions focused on primordial and primary prevention for young adults, 1,29 given evidence that cardiovascular disease mortality may now be rising in this population, as well as the potential adverse long-term public health impact of these trends in risk factors on lifetime rates of acute myocardial infarction, stroke, and heart failure. [17][18][19]30 We also observed significant variation in cardiovascular risk factors across racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…CVD is the leading cause of death and morbidity in people with diabetes [ 18 ]. The incidence of CVD in young adults is increasing and has been linked to several variables, including obesity, overweight, tobacco use, and unhealthy diet, suggesting that the disease is not confined to a specific age group [ 19 ]. The impact of CVD is also observed in different geographical regions, as studies have reported different prevalence rates of CVD in different populations, including rural and urban settings [ 20 ].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…T he intersection of maternal and child cardiovascular health is a critical yet often underexplored frontier in the efforts to addressing cardiovascular disease (CVD). The rising prevalence of CVD in younger adults, with up to 40% of those younger than 50 years, and the alarming 27% rate of hypertension in children and adolescents aged 11 to 17 years 1,2 are increasingly concerning. This underscores the urgent need to reconsider the approach to CVD care and prevention.…”
mentioning
confidence: 99%